Problem of staffing shortage in the Ulyanovsk region of the Russian Federation and some ways to solve it - D. A. Mukhametov (Вестник университета)
The article examines the problem of personnel shortage in the Ulyanovsk region in the context of current economic and political transformations. The reasons for the shortage of qualified specialists are analysed, which include both positive factors (rapid economic development and technological changes) and negative ones (demographic changes, industry characteristics, imbalance in the labour market and migration). Statistical data on the level of unemployment, migration, and population structure are provided, which makes it possible to identify the main trends and predict the further development of the situation in the labour market. Particular attention is paid to the problem of migration of graduates of higher educational institutions and their impact on the economy of the region. The article also examines the impact of international and interregional migration on the labour market and demographic situation in the region. Possible ways to solve the problem of the personnel shortage are discussed, including improving the material and technical base of educational institutions, adapting educational programmes to the requirements of the labour market, and introducing a multi-level system of control over the migration. The proposed measures are aimed at creating conditions for attracting and retaining the qualified specialists in the region, which in turn will contribute to its sustainable economic development.